Psychometric Properties of the Spanish Version of the Tampa Scale for Kinesiophobia (TSK). - Gómez-Pérez, Lydia; López-Martínez, Alicia Eva; Ruiz-Párraga, Gema Teresa (Elsevier, 2011)
The Tampa Scale for Kinesiophobia (TSK) is one of the most frequently employed measures for assessing pain-related fear in pain patients. Although the TSK has been translated into different languages, a Spanish version of the TSK has not been available, up to now. Thus, the aim of this study was to validate the Spanish version of the TSK in 2 different pain samples: A heterogeneous chronic pain sample (n = 125) and a musculoskeletal acute pain sample (n = 86). Factor analysis revealed a 2-factor model of 11 items replicated on both samples, named TSK-11. The instrument obtained shows good reliability (internal consistency and stability) and validity (convergent and predictive), with the advantage of brevity. Evidence is provided on discriminant validity between both TSK factors (called Activity Avoidance and Harm). The Harm factor shows the best predictive validity, as it predicts pain persistence, catastrophizing, depression, and pain intensity scores after 6 months. Changes in the Activity Avoidance factor are positively correlated with changes in catastrophizing and anxiety, and negatively associated with changes in functional status. The results of this study point to the relative contribution of both components of pain-related fear to pain adjustment. Perspective: This article presents the Spanish version of the TSK. Factor analysis revealed a 2-factor model (called Activity Avoidance and Harm). The version obtained shows good reliability and validity. Results provide clinicians with access to a measure of pain-related fear for Spanish-speaking pain patients, offering the advantage of brevity.
https://openpolicyfinder.jisc.ac.uk/id/publication/14183
Keywords: Dolor - Aspectos psicológicos; Fobias; Psicometría; Spanish; Tampa Scale for Kinesiophobia; Chronic and acute pain; Factor structure; Validity